2020
DOI: 10.22452/mjlis.vol25no3.5
|View full text |Cite
|
Sign up to set email alerts
|

The explanatory power of social capital in determining knowledge sharing in higher education: A case from Saudi Arabia

Abstract: Knowledge sharing strengthens individual creativity, critical thinking and innovation. It also improves research and development endeavors, performance and productivity at the organizational level. Knowledge sharing decreases the amount of red-tape faced by organizations, firms and individuals in achieving economic, as well as social improvements. Notwithstanding the plethora of empirical studies on knowledge sharing determinants, much confusion has been produced by differing conclusions. Using original data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
2
5
0
1
Order By: Relevance
“…The suggested and demonstrated links between TLH activities and expected student learning outcomes in this study, are consistent with findings in other studies which suggest associations between student learning outcomes and collaborative learning such as cognitive, inter-professional, and team skills (Michaelsen et al, 1993;Haidet et al, 2002); improved positive student attitudes and motivation (Gomez et al, 2010;McInerney and Fink, 2003); critical thinking, creativity and innovation (Almuqrin et al, 2020); and overall improved academic performance and relationships in the learning community when compared to traditional learning (Carpenter et al, 2022;Cremerius et al, 2021;Eskeen, 2019;Venter, 2019).…”
Section: Achievement Of Tlh Outcomessupporting
confidence: 90%
See 1 more Smart Citation
“…The suggested and demonstrated links between TLH activities and expected student learning outcomes in this study, are consistent with findings in other studies which suggest associations between student learning outcomes and collaborative learning such as cognitive, inter-professional, and team skills (Michaelsen et al, 1993;Haidet et al, 2002); improved positive student attitudes and motivation (Gomez et al, 2010;McInerney and Fink, 2003); critical thinking, creativity and innovation (Almuqrin et al, 2020); and overall improved academic performance and relationships in the learning community when compared to traditional learning (Carpenter et al, 2022;Cremerius et al, 2021;Eskeen, 2019;Venter, 2019).…”
Section: Achievement Of Tlh Outcomessupporting
confidence: 90%
“…TBL, as an advanced collaborative strategy, makes small group work the primary in-class activity and calls for activities that support the transformation of newly formed groups into high-performance learning teams, and usually requires a change in the structure of the team and transforms teamwork from a technique to a strategy (Fink, 2002;Michaelsen and Sweet, 2008;Parmelee et al, 2012). TBL and other collaborative learning environments advance student learning outcomes such as cognitive, inter-professional and team skills (Michaelsen et al, 1993;Haidet et al, 2002); positive student attitudes and motivation (Gomez et al, 2010;McInerney and Fink, 2003); as well as critical thinking, creativity, and innovation (Almuqrin et al, 2020). In general, team learning contributes to overall improved academic performance and relationships in the learning community when compared to traditional learning (Carpenter et al, 2022;Cremerius et al, 2021;Eskeen, 2019;Venter, 2019).…”
Section: Literature Review Tlh Student Learning Communitiesmentioning
confidence: 99%
“…The sheer scale of this migration movement has created a new generation of demographics that continues to attract attention. Specifically, in the urban centers, the 2010 national census reported that there were as many as 35.81 million migrant children [ 3 , 4 ]. Historically, the growth of this population saw an increment of 27.80% between 2000 and 2005 and 41.37% in the period 2005 to 2010 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To better understand knowledge sharing in higher education institutions, numerous empirical research was performed in a range of contexts, including Malaysia (Fauzi, 2023;Fauzi, Nya-Ling, et al, 2018Fauzi, Tan Nya-Ling, et al, 2019;Hosen et al, 2020;Rahman et al, 2018), Bangladesh (Rahman et al, 2018(Rahman et al, , 2021, Hongkong (Lo & Tian, 2020), Pakistan (Bibi & Ali, 2017;Javaid et al, 2020), Portugal (Chedid et al, 2020(Chedid et al, , 2022, United Kingdom (Fullwood & Rowley, 2017), and Saudi Arabia (Almurqin et al, 2020). Some theories were popularly used to analyse determinants of knowledge sharing among academician, such as: Theory of Reasoned Action (Chedid et al, 2020;Fullwood & Rowley, 2017), Theory of Planned Behavior (Fauzi, Nya-Ling, et al, 2018Fauzi, Tan Nya-Ling et al, 2019;Hosen et al, 2020), and Social Capital Theory (Fauzi, Nya-Ling, et al, 2018Fauzi, Tan Nya-Ling, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%